2013
DOI: 10.1089/dna.2013.2061
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Insertion/Deletion Polymorphism in the Promoter of PDCD6IP Is Associated with the Susceptibility of Hepatocellular Carcinoma in a Chinese Population

Abstract: Hepatocellular carcinoma (HCC) is one of the most common malignancies worldwide. Apart from environmental factors such as hepatitis B virus (HBV) or hepatitis C virus, alcohol abuse, and exposure to dietary aflatoxin, genetic factors are also involved in the pathogenesis of HCC. By analyzing 390 HCC cases and 431 healthy controls in a Chinese population, we used a candidate gene approach to evaluate the association between a 15-bp insertion/deletion (indel) polymorphism (rs28381975) in the promoter region of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…Insertions and deletions (indels) are the second most common type of human genetic variants after single nucleotide polymorphisms (SNP) [19]. Many human inherited diseases have been reported to be related to indels [20, 21]. Recent results show that the indel rate in the human genome is approximately 1 in 3000 bp [22].…”
Section: Introductionmentioning
confidence: 99%
“…Insertions and deletions (indels) are the second most common type of human genetic variants after single nucleotide polymorphisms (SNP) [19]. Many human inherited diseases have been reported to be related to indels [20, 21]. Recent results show that the indel rate in the human genome is approximately 1 in 3000 bp [22].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in liver cancer, we predicted 41 driver proteins that were significantly mutated at lysine modification motifs. Eight (19.5%) of these proteins were reported previously as cancer drivers (Friedenson, 2005 ; Silvera et al, 2010 ; Zhou et al, 2011 ; Chang et al, 2013 ; Yu et al, 2013 ; Pandey et al, 2016 ; Miao et al, 2017 ; Tang et al, 2017 ). In particular, HOXC10 was known to be associated with a decrease in the overall survival rate of liver cancer (Tang et al, 2017 ).…”
Section: Resultsmentioning
confidence: 96%
“…To date, there have only been two reports that investigated the association between PDCD6IP 15 bp I/D and cancer risk. Yu et al [ 22 ] evaluated the possible association between the PDCD6IP 15 bp I/D polymorphism and hepatocellular carcinoma (HCC). They found that subjects carrying I/D or I/I genotype had a significantly increased risk for HCC compared to individuals carrying the D/D genotype (OR = 1.39, 95% CI = 1.01–1.91, p = 0.033).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, little information is available regarding the association between PDCD6IP polymorphisms and cancer risk [ 9 , 22 ]. To the best of our knowledge, there are no reports regarding the association between the 15 bp I/D variant within the PDCD6IP promoter and BC susceptibility.…”
Section: Introductionmentioning
confidence: 99%